Haemolytic studies on Fish, Sheep and Human Blood Agar against Pathogenic Bacteria - Nadella, Ranjit Kumar; V. A., Minimol; Nilavan, Ezhil; Muthulakshmi, T.; Basha, K. Ahamed; Prasad, M. M. (Fishery Technology, 2020)
In this study, Î²-haemolytic activity of fish blood(Cyprinus rubrofuscus), sheep blood (SB) and humanblood (HB) was assessed for studying haemolysisagainst reference bacterial strains Edwardsiella tarda(ATCC 15947); Aeromonas hydrophila (ATCC 35654);Enterobacter cloacae (ATCC 13047); Pseudomonasaeruginosa (ATCC 10145); Escherichia coli (ATCC35218); Staphylococcus aureus (ATCC 43300); Vibriocholera (MTCC 3906) and Salmonella paratyphii(ATCC 15305). Both human blood and fish bloodshowed similar Î²-haemolytic activity for all pathogensexcept E. cloacae on fish blood. The zone ofhaemolysis (mm) recorded in FB is 18, 28, 0, 22, 25,14, 20, 22; in HB is 13, 15, 14, 23, 17, 18, 15, 17 andin SB is 14.6, 13.8, 15.8, 26.2, 19.4, 21.2, 17.6, 16.2after 48 h respectively for E. tarda; A. hydrophila; E.cloacae; P. aeruginosa; E. coli; S. aureus; V. cholera andS. paratyphii. The present study also reports theantimicrobial property of fish blood against thecommonly occurring fish pathogens. The resultindicated a decrease in optical density readings infish blood supplemented broth compared to controlbroth (without blood). This indicates clear inhibitionof growth for the three pathogens in BHI brothsupplemented with fish blood possesed due to thepresence of antimicrobial substances in the fishblood. In conclusion, Î²-haemolytic activity observedbetter in FB plates when compared with HB platesand therefore, fish blood can be used as analternative to sheep blood for haemolytic studies offish pathogens.